If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-5x+3)=-14(x+1)
We move all terms to the left:
3(-5x+3)-(-14(x+1))=0
We multiply parentheses
-15x-(-14(x+1))+9=0
We calculate terms in parentheses: -(-14(x+1)), so:We get rid of parentheses
-14(x+1)
We multiply parentheses
-14x-14
Back to the equation:
-(-14x-14)
-15x+14x+14+9=0
We add all the numbers together, and all the variables
-1x+23=0
We move all terms containing x to the left, all other terms to the right
-x=-23
x=-23/-1
x=+23
| -2x+5+6x+1=-2x+6x+10 | | 7x-3-6x=5+22 | | 7x-3-6x=24+3 | | 4z/7-9=7 | | (-3x)-4=2x-14 | | x/9-8=0 | | 3(x+2)2=15 | | x=3x+5-(2x-9) | | 3(x-5)+7=0 | | -x+13=-27 | | 2x–7=3x+2 | | 5n-9=43 | | 16(7)=14x(8x) | | x-10+4x-25+x-5=180 | | 8x+2=6x-1+7x+7 | | 11x−24=3x | | 7x+3/2=4x-5/3 | | 8^(2x-1)=35^x | | 8^2x-1=35^x | | 7x^2+18x=193 | | 3(5x-3)=2x-35 | | 7x-1=3x+47 | | 0.08t+0.11(100-t)=9.8 | | 5.6=3.2x+13.2 | | 5-3(2-x)=1 | | z-3,5z+1,2=-0,3 | | (4x-3)(3x+2)-2=(6x-7)(2x-5) | | 1-49x²=0 | | 1.5x+4=56 | | 1/2x+4*x=56 | | 5(x+5)=3(x-4) | | -(2x-1)(3x+5)=50-6x(x-3) |